The impact of risk governance and capital requirement on bank stability in Nigeria - David, Fajembola Olusola (2020)
This study investigates the impact of risk governance and capital requirement on bank stability in Nigeria. The data was obtained through collection of 214 company-year observations for the period of 2006-2017, which coincided with the implementation of the code of governance for banks. It covers eleven years after the issuance of the code of governance. All deposit money banks in Nigeria were used as samples for the study. Bank stability was measured by Z-Score, risk governance attributes by the risk management committee (RMC), audit committee (AC) and the board of director; while capital requirement ratio (CARR) was measured by capital adequacy. Besides that, capital requirement ratio was also considered as the measurement for the external governance. By using the multiple regression analysis, results revealed that with respect to the RMC, only the size has positive and significant relationship with bank stability. Similarly, for the AC, only the expertise has significant relationship and positively affect bank stability; meanwhile for board structure, the only positive attribute was gender. Also, results showed that the board and its risk governance committees did not effectively promote bank stability in Nigeria. However, results revealed that capital requirement had a significant positive relationship with bank stability, thus suggesting that CARR is an important external mechanism especially for banking sector. Moreover, risk governance practices in the Nigerian banking industry have low influence on bank stability. The findings showed the weaknesses in the central bank supervision of banks, which contributed to the slack in internal governance. The policy implications arising from these findings suggested a review of the code of governance to strengthen the central bank’s supervision, increase the number of women on the boards and legal reforms to strengthen the courts on the enforcement of the codes.